Narrowing the gap: correlating street width and pedestrian safety to justify narrowing urban streets - Gorrell, Casey (Kansas State University, 2014)
Many cities in the United States have developed into auto-dominated places with decreased accessibility for pedestrians and bleak cityscapes of wide, barrier-like streets. While many studies exist on the correlation between street width and vehicular safety, and vehicular speed and pedestrian safety, little information is available on the correlation between street width and pedestrian safety. This project began while the researcher interned with the New York City Department of Transportation (NYCDOT) Pedestrian Projects Group (PPG). The researcher was asked to begin a study of New York City (NYC) streets, specifically analyzing the relationship between street width and pedestrian safety using NYC safety data. The street types studied represent a variety of conditions found in many cities. The exploratory correlation study, completed after returning to Kansas State University, found that narrow streets trend towards higher safety. The correlation study between street width and pedestrian safety provides justification to narrow Bluemont Avenue in Manhattan, Kansas and increase pedestrian safety. Bluemont Avenue is a primary vehicular connection between the east and west sides of Manhattan. The city’s future construction plans propose widening the street to accommodate a center turning lane along the entire length of Bluemont Avenue. The research presented in this report supports the hypothesis that narrower streets are safer for pedestrians. By utilizing the results of the study, a designer can strengthen their argument to narrow wide, auto-dominated streets. In addition, the use of a two-stage design process can create a safer environment for pedestrians on Bluemont Avenue. By utilizing a temporary design followed by a permanent installation, the City of Manhattan can decrease the priority of Bluemont Avenue within the vehicle hierarchy and increase pedestrian safety. The intent of this report is to begin a conversation with the City of Manhattan to begin looking at streets not as mere vehicular paths, but paths for all modes of transit.
Keywords: Landscape Architecture; Streets; Pedestrian; Transportation; New York City; Landscape Architecture (0390)